Maintenance of the bronchial alveolar stem cells in an undifferentiated state by secreted frizzled‐related protein 1. Issue 12 (11th September 2014) - Shiomi, Takayuki; Sklepkiewicz, Piotr; Bodine, Peter V. N.; D'Armiento, Jeanine M.
Abstract : Bronchoalveolar stem cells (BASCs) are mobilized during injury and identified as lung progenitor cells, but the molecular regulation of this population of cells has not been elucidated. Secreted frizzled‐related protein 1 (SFRP1) is a critical molecule involved in alveolar duct formation in the lung and here we demonstrate its importance in controlling cell differentiation during lung injury. Mice lacking SFRP1 exhibited a rapid repair response leading to aberrant proliferation of differentiated cells. Furthermore, SFRP1 treatment of BASCs maintained these cells in a quiescent state. In vivo overexpression of SFRP1 after injury suppressed differentiation and resulted in the accumulation of BASCs correlating with in vitro studies. These findings suggest that SFRP1 expression in the adult maintains progenitor cells within their undifferentiated state and suggests that manipulation of this pathway is a potential target to augment the lung repair process during disease.—Shiomi, T., Sklepkiewicz, P., Bodine, P. V. N., D'Armiento, J. M., Maintenance of the bronchial alveolar stem cells in an undifferentiated state by secreted frizzled‐related protein 1. FASEB J. 28, 5242–5249 (2014). www.fasebj.org